Test-retest Variability of [(11)C]Raclopride Binding Potential in Nontreatment-Seeking Alcoholics - Yoder, Karmen K. (2010)
Knowledge of the reproducibility of striatal [(11)C]raclopride (RAC) binding is important for studies that use RAC PET paradigms to estimate changes in striatal dopamine during pharmacological and cognitive challenges. To our knowledge, no baseline test-retest data exist for nontreatment-seeking alcoholics (NTS). We determined the test-retest reproducibility of baseline RAC binding potential (BP(ND)) in twelve male NTS subjects. Subjects were scanned twice with single-bolus RAC PET on separate days. Striatal RAC binding potential (BP(ND)) for left and right dorsal caudate, dorsal putamen, and ventral striatum was estimated using the Multilinear Reference Tissue Method (MRTM) and Logan Graphical Analysis with a reference region (LGA). Test-retest variability (TRV), % change in BP(ND) between scan days, and the intraclass correlation coefficient (ICC) were used as metrics of reproducibility. For MRTM, TRV for striatal RAC binding in NTS subjects was ± 6.5%, and ± 7.1% for LGA. Average striatal ICCs were 0.94 for both methods (p < 0.0001). Striatal BP(ND) values were similar to those reported previously for detoxified alcoholics. The results demonstrate that baseline striatal RAC binding is highly reproducible in NTS subjects, with a low variance similar to that reported for healthy control subjects.